2022
DOI: 10.3389/fonc.2022.882300
|View full text |Cite
|
Sign up to set email alerts
|

An MRI-based pelvimetry nomogram for predicting surgical difficulty of transabdominal resection in patients with middle and low rectal cancer

Abstract: ObjectiveThe current work aimed to develop a nomogram comprised of MRI-based pelvimetry and clinical factors for predicting the difficulty of rectal surgery for middle and low rectal cancer (RC).MethodsConsecutive mid to low RC cases who underwent transabdominal resection between June 2020 and August 2021 were retrospectively enrolled. Univariable and multivariable logistic regression analyses were carried out for identifying factors (clinical factors and MRI-based pelvimetry parameters) independently associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Appropriate pelvic debridement and total mesorectal excision (TME) are essential to prevent local recurrence [ 20 ]. Previous studies have focused on the consequence of pelvic factors and rectal mesenteric fat area on the surgical outcome of lower and middle rectal cancer [ 21 , 22 ], the consequence of a large vertical pelvic depth, a small pelvis, a short transverse meridian, a large sacrococcygeal curvature and a high rectal mesenteric fat area on the difficulty of the procedure was also determined [ 17 , 23 , 24 ], and these factors are particularly significant for men [ 25 ]. However, the relationship between quantitative pelvic measurements and surgical difficulty is uncertain, and some studies have even found no association between pelvic measurements and surgical difficulty [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate pelvic debridement and total mesorectal excision (TME) are essential to prevent local recurrence [ 20 ]. Previous studies have focused on the consequence of pelvic factors and rectal mesenteric fat area on the surgical outcome of lower and middle rectal cancer [ 21 , 22 ], the consequence of a large vertical pelvic depth, a small pelvis, a short transverse meridian, a large sacrococcygeal curvature and a high rectal mesenteric fat area on the difficulty of the procedure was also determined [ 17 , 23 , 24 ], and these factors are particularly significant for men [ 25 ]. However, the relationship between quantitative pelvic measurements and surgical difficulty is uncertain, and some studies have even found no association between pelvic measurements and surgical difficulty [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al. ( 25 ) developed a nomogram to predict the difficulty of rectal surgery. However, it’s worth noting that this nomogram model did not include MFA, which has been reported to be an important factor in the difficulty of rectal surgery ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using multivariate analysis, they found the factors significantly associated with surgical difficulty were BMI, pelvic inlet and intertuberous distance, and a nomogram model was established with the selected parameters for predicting the probability of high surgical difficulty. This objective method would provide a visualization tool to effectively predict the probability of surgical difficulty in RC [ 21 ]. Similarly, the study of T. Yamamoto et al also used multiple criteria to comprehensively define the difficulty of surgery [ 47 ].…”
Section: Discussionmentioning
confidence: 99%